The role of organic amendments and no-tillage in enhancing soil health: insights from a 34-year field experiment - Mushtaq, Muazzama (My University, 2025)
The rising challenges of climate change have emphasized the urgent need for sustainable agricultural practices that promote long-term soil health and productivity. This thesis evaluates the impact of 34 years of tillage and nitrogen sources on soil carbon (C) and nitrogen (N) storage, biological activity, and overall soil health at the Kansas State University Agronomy North Farm. A split-plot randomized block design with four replications was employed, with two tillage systems: no-till (NT) and conventional tillage (T) as the main plots, and three nitrogen sources (compost, urea, and control) as the subplots. Soil samples were collected to a depth of 90 cm and analyzed for chemical, biological, and microbial properties. Long-term application of compost (OF) significantly enhanced C and N storage in 0–30 cm of soil. Although the no-till system with OF improved storage compared to conventional tillage, the difference was only significant in the 0-5 cm layer. As C and N reached effective saturation with compost at the 0-5 cm depth, there was translocation of C and N to the 5-15 cm layer, and subsequently to the 15-30 cm layer. No-till also supported deeper root growth (up to 45–60 cm) and reduced C and N losses in subsurface layers compared to conventional tillage. Enzyme activities (β-glucosidase, N-acetylglucosaminidase, acid phosphatase, and arylsulfatase) were highest in the upper 0–30 cm depth and were consistently greater with compost. No-till further increased enzyme activity compared to conventional tillage, although the differences were not always significant. Compost also supported higher microbial biomass, including fungi, bacteria, and actinomycetes, with stronger effects under no-till. Interestingly, arbuscular mycorrhizal fungi (AMF) were more abundant where no N had been applied for 34 years, suggesting that reduced inputs may create the need for AMF. Enzyme activity and microbial biomass were positively correlated with soil C and N levels, reflecting the strong link between organic matter availability and soil biological function. Overall, long-term implementation of no-till and organic fertilizer improved soil health by increasing nutrient retention, enhancing microbial activity, and promoting C and N storage in the soil. These changes contribute to the development of more stable and resilient soil systems, capable of supporting sustainable crop production. Furthermore, increased soil C and N storage play a crucial role in mitigating climate change by reducing atmospheric greenhouse gas emissions. Therefore, the combined use of no-till and compost represents an effective management strategy to enhance soil function, improve agricultural sustainability, and address environmental challenges associated with climate change.
Keywords: Soil organic carbon; Soil enzymes; Microbial biomass; Deep soil; Long term